Accuracy and precision comparison with elemental analysis parameter optimization for XRF, OES, and SEM-EDS - Kallio, Matias (My University, 2025)
Scanning Electron Microscope (SEM) with Energy Dispersive Spectrometer (EDS) is a widely used technique in various industries and applications due to its ability to image nanoscale structures with high resolution. EDS enhances the use of SEM as it produces qualitative and quantitative information based on characteristic X-rays emitted from the sample. Optical Emission Spectroscopy (OES) and X-ray fluorescence (XRF) are mature techniques for high-quality and fast elemental analysis with quick sample preparation. This thesis investigates the accuracy and precision of elemental analysis techniques, including SEM-EDS, OES, and XRF. Experimental analysis also focuses on different surface qualities, such as cones, grooves or fracture surface and aims to determine the optimal parameters in elemental analysis for each technique. Furthermore, the purpose is to explore the effects of different surface qualities and determine the optimal parameters in that scope that is possible in these circumstances. Results obtained in this study indicate the superior performance of OES in quantitative elemental analysis for both major and trace elements, highlighting the SEM-EDS capabilities for examining specially shaped samples, such as cones, grooves, and fracture surfaces. XRF exceeded the performance of EDS in quantitative analysis and precision, but limitations occurred with light elements (Z < 11) and accuracy. Overall, the study gives detailed insights into characterization and operation of different elemental analysis techniques highlighting the importance of sample preparation and correct operational parameters.
Keywords: Chemical analysis, Scanning Electron Microscope, Energy Dispersive Spectroscopy, Optical Emission Spectroscopy, X-ray fluorescence, Accuracy, Precision